2023
DOI: 10.1186/s12891-023-06368-z
|View full text |Cite
|
Sign up to set email alerts
|

Standard radiographic values for the acetabulum in Japanese adolescents: a cross-sectional study

Abstract: Background Most previous reports of normal acetabular radiographic values focused on adults or elderly people. Recent reports have described premature hip osteoarthritis in adolescents not caused by acetabular dysplasia. In addition, there is a certain failure rate of surgical treatment for young patients with borderline acetabular dysplasia. Accurate indices for treatment of adolescent hips are unclear because standard measurement values of the adolescent acetabulum have not been reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Also, Japanese adolescents had slightly lower mean values of LCEA (27.5°) than in the present study. 29 Consequently, the present results of the low prevalence of acetabular dysplasia after NHI apply to Europe. Previous studies have suggested a tendency in patients treated for DDH to develop dysplasia during growth.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Also, Japanese adolescents had slightly lower mean values of LCEA (27.5°) than in the present study. 29 Consequently, the present results of the low prevalence of acetabular dysplasia after NHI apply to Europe. Previous studies have suggested a tendency in patients treated for DDH to develop dysplasia during growth.…”
Section: Discussionmentioning
confidence: 58%
“…Two recent Japanese studies reported a similar mean value for the AHI compared with that found in the present study. 18,29 Nishimura et al reported an even higher mean SA and speculated whether the propensity for dysplastic values was caused by the young age (12 to 18 years) of the participants in their cohort. 29 The clinical significance of these findings is unknown as the most important measurement for acetabular dysplasia, LCEA, did not indicate a higher rate of dysplasia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the center of focus changed slightly depending on the growth in height. However, we reported previously that there is no significant effect of height of body on the problems of using whole-spine radiographs for evaluating the acetabular parameters [ 30 ]. Regarding the fact that one investigator performed the measurements, in the same previous study, we reported intra-rater reliability of more than moderate for LCEA, Sharp angle, Tönnis angle, and AHI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%